How Does Push-Off Distance Influence Force–Velocity Profile and Performance During Vertical Jumping? - Pommerell, Félicie; Boyas, Sébastien; Samozino, Pierre; Morel, Baptiste; Begue, Jérémie; Rahmani, Abderrahmane; Peyrot, Nicolas (Journal of Applied Biomechanics, 2025)
In many sports, practitioners must reach their maximal jump height (hmax) under time constraints. This requires a reduction of the countermovement depth and so of the push-off distance (hPO). The purpose of this study was to investigate how hPO influences force–velocity (F–v) profiles ( F ¯ 0 , v ¯ 0 , P ¯ max , and SFv) and performance. Eleven participants (age: 26 [5] y, height: 175.6 [11.2] cm, mass: 76 [15] kg; squat 1RM: 129 [34] kg) performed maximal countermovement jumps. Kinetic and kinematic measurements were used to assess individual F–v profiles for 3 different hPO conditions (hPO-SMALL, hPO-MEDIUM, hPO-LARGE) from countermovement jumps performed under different load conditions (bodyweight [BW], BW + 8 kg, BW + 17 kg, BW + 40%1RM, BW + 70%1RM). Results indicated that F ¯ 0 and P ¯ max changed across hPO conditions, while v ¯ 0 remained constant. A lower hPO led to a significantly higher F ¯ 0 and P ¯ max . These changes resulted in a steeper SFv leading to a more force-oriented profile, a lower optimal SFv and a greater F–v imbalance. Reducing hPO and modifying F–v profile led, to some extent, to a reduction in hmax. Performance is a compromise between hPO, P ¯ max , and F–v imbalance, all influenced by countermovement depth. This explains why reducing countermovement depth to meet time constraint may lower performance.